Just-in-Time Electronic Health Record Retraining to Support Clinician Redeployment during the COVID-19 Surge - Jin, Da P.; Samuel, Sunil; Bowden, Kristin; Mohan, Vishnu; Gold, Jeffrey A. (Applied Clinical Informatics, 2022)
Background In response to surges in demand for intensive care unit (ICU) care related to the COVID-19 pandemic, health care systems have had to increase hospital capacity. One institution redeployed certified registered nurse anesthetists (CRNAs) as ICU clinicians, which necessitated training in ICU-specific electronic health record (EHR) workflows prior to redeployment. Under time- and resource-constrained settings, clinical informatics (CI) fellows could effectively be lead instructors for such training.Objective This study aimed to deploy CI fellows as lead EHR instructional trainers for clinician redeployment as part of an organization's response to disaster management.Methods CI fellows led a multidisciplinary team alongside subject matter experts to develop and deploy a tailored EHR curriculum comprising in-person classes and online video modules, leveraging high-fidelity simulated patient cases. The participants completed surveys immediately after the in-person training session and after deployment.Results Eighteen CRNAs participated, with 15 completing the postactivity survey (83%). All felt the training was useful and improved their EHR skills with a Net Promoter score of +87. Most (93%) respondents indicated the pace of the session was “just right,” and 100% felt the clarity of instruction was “just right” or “extremely easy” to understand. Twelve participants (67%) completed the postdeployment survey. The training increased comfort in the ICU for all respondents, and 91% felt the training prepared them to work in the ICU with minimal guidance. All stated that the concepts learned would be useful in their anesthesia role. Fifty-eight percent viewed the online video library.Conclusion This case report demonstrates that CI fellows with dual domain expertise in their clinical specialty and informatics are uniquely poised to deliver clinician redeployment EHR training in response to operational crises. Such opportunities can achieve fellowship educational goals while conserving physician resources which can be a strategic option as organizations plan for disaster management.
Keywords: electronic health records; computer simulation; COVID-19; professional role; graduate medical education